Metaphor in Billie Eilish’s Song “Happier Than Ever”: A Semantic Analysis - Alika Marsya Salsabila; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to identify and analyze the use of metaphors in the song Happier Than Ever by Billie Eilish through a semantic approach. Previous studies, such as those conducted by Chanty, Nurhapitudin, and Huznatul (2025), discussed the lexical and metaphorical meanings in Wildflower songs, while Theodora and Setiawan (2024) analyzed various types of figurative language in songs such as Lunch, TV, and Bird of a Feather. However, these studies focus on different songs and have not examined in depth the metaphors in the song Happier Than Ever. This research fills that void by highlighting one song in particular to see how metaphors function and influence meaning in the lyrics. Using a qualitative descriptive method, this study found seven metaphorical expressions. The analysis shows that these metaphors emphasize the themes that represent emotional pain, disappointment, and efforts to understand meaning in the dynamics of personal relationships. The use of metaphors not only embellishes the lyrics, but also allows Billie Eilish to express complex emotions with more depth and meaning.